The Effect of Product Quality, Influencer Role, and Live Streaming Features on Consumer Purchase Decisions for Skincare Products on Tiktok Social Media - Gita Suci Indah Cahyani; Pujiarti Pujiarti (eCo-Fin, 2025)
is study aims to test how much product quality influences the role of influencers, and live streaming features have on purchasing decisions for skincare products on TikTok social media. The population in this study was 138 respondents with a random sampling method. From the results of the Determination Coefficient (R^2) test, the Adjusted R Square (R^2) value is 33.3%, while the remaining 66.7% is influenced by other factors. The t count value for product quality is greater than the t table, which is 1.772 > 1.656 with a significant value of 0.000 < 0.05. The t count value for the role of influencers is known to be greater than the t table, which is 3.990 > 1.656 with a significance value of 0.000 < 0.05. The t count value for the live streaming feature is known to be greater than the t table, which is 3.453 > 1.656 with a significant value of 0.000 > 0.05. This means that product quality, the role of influencers, and live streaming features have a significant effect on the decision to purchase skincare products. Based on the F count value on product quality, the role of influencers, and live streaming features of 23.776 with a significant level of 0.000 where the number 0.000 < 0.05 and > or 23.776 > 2.28. So, it can be concluded that Ho is rejected, and Ha is accepted which means there is a simultaneous influence between variables on product quality, the role of influencers, and live streaming features on the decision to purchase skincare products.